A scoping review of maternal and neonatal health services impacted during COVID-19 in Nepal - Gaire Sampada; Dilip Bhandari; Chika Yamamoto; Tianchen Zhao; Masaharu Tsubokura (Journal of Global Health Reports, 2023)
# Background